Preclinical Evaluation of a Zinc Oxide Nanoparticle–Loaded Amniotic Membrane as a Bioactive Scaffold for Partial‐Thickness Burn Healing in Rats. - Hashemi, Seyedeh-Sara; Mohammadi, Ali-Akbar; Jalali, Seyed Behzad; Mosalamiaghili, Seyedarad; Rafati, Alireza; Ghaedi, Mojtaba; De Molon, Rafael Scaf (BioMed Research International, 2026)
Burn wound infections continue to be a leading cause of morbidity and mortality despite advancements in medical treatments. Human amniotic membrane and zinc oxide nanoparticles have individually shown promise in enhancing wound healing. This study evaluated the efficacy of a novel composite scaffold made of zinc oxide nanoparticles–impregnated human amniotic membrane for treating second‐degree burn wounds. Human amniotic membrane was isolated from cesarean‐delivered placentas and loaded with nanoparticles via ultrasonic dispersion. The composite scaffold was characterized using scanning electron microscopy and energy‐dispersive x‐ray spectroscopy, which confirmed uniform nanoparticle distribution. Human fibroblast cell culture studies demonstrated enhanced cell viability and adhesion in the composite scaffold compared with controls. In a rat model of second‐degree burns, the nZnO‐impregnated human amniotic membrane significantly improved wound healing, evidenced by faster reepithelialization, reduced inflammation, and complete tissue regeneration by Day 14. These findings suggest that the combination of nZnO and human amniotic membrane offers superior wound healing properties over traditional treatments, with potential applications for burn care. Future studies should explore human trials to further validate the clinical potential of this novel approach.